Motivación de los trabajadores y calidad de servicio en un Centro de Idiomas de Trujillo, año 2022 - Gonzales Ruiz, Juan Carlos (2022)
The main objective of this research was to evaluate the relationship between the employee motivation and the quality of service in a language centre in Trujillo in 2022, following a quantitative approach study, correlational level and non experimental methodological design, where 74 employees and the same proportion of students of this language centre were taken into account as the study population, using the survey technique to collect data. As for the most important results, it was found that 28.4% of teachers had low levels of motivation, while 25.7% said that the quality of service was poor. In conclusion, the general hypothesis of the study was proven, demonstrating at a statistical level that there is a direct relationship between the motivation of the workers and the quality of service in a language centre in Trujillo in 2022, meaning that the greater the motivation in this study population, the greater the perception of the quality of service.